DETERMINATION OF ESTERASE TYPE OF POLY LACTIDE DEPOLYMERASE FROM A COMPOST THERMOPHILE - S. PREMA; P. UMA MAHESWARI DEVI (The Bioscan, 2012)
Compost samples were screened for isolation of PLA degrading thermophilic bacteria by the standard clear zone method at 50ºC and the degradation was observed on 20th day of incubation. The thermophilic isolate was identified as a Gram positive, rod shaped, non capsulated and spore forming bacterium. Based on biochemical characteristics and 16S rDNA gene sequence analysis the isolate was identified as Bacillus licheniformis. The PLA depolymerase was extracted and characterized as an esterase. The present study among the inducers tributyrin and PLA showed remarkable induction in esterase type of PLA depolymerase in Bacillus licheniformis on comparison with casein and gelatin